Detection of Albumin Expression by RNA In Situ Hybridization Is a Sensitive and Specific Method for Identification of Hepatocellular Carcinomas and Intrahepatic Cholangiocarcinomas. Issue 1 (9th May 2018) - Lin, Fan; Shi, Jianhui; Wang, Hanlin L; Ma, Xiao-Jun; Monroe, Robert; Luo, Yuling; Chen, Zongming; Liu, Haiyan
Abstract: Objectives: Inconsistent data on detection of albumin expression by ribonucleic acid (RNA) in situ hybridization have been reported. We investigated the utility of RNAscope (Advanced Cell Diagnostics, Hayward, CA) in detection of albumin in hepatocellular carcinomas (HCCs), intrahepatic cholangiocarcinomas (ICCs), and carcinomas from various organs using manual and automated staining. Methods: RNAscope for albumin detection was performed on 482 cases on tissue microarray sections and on 22 cases of ICC, including 14 surgical resection and eight core biopsy specimens. Results: Thirty-six of 37 (97%) HCCs had detectable mRNA, whereas all non-HCC and non-ICC cases, except one lung adenocarcinoma, were negative for albumin. Fourteen of 22 ICCs (64%) were positive for albumin. Conclusions: RNAscope for albumin is highly sensitive and specific for identifying HCCs and is highly specific and moderately sensitive for detection of ICCs; however, rare carcinomas (non-HCC, non-ICC, and those with no hepatoid histomorphology) can also have aberrant expression of albumin.